2022
DOI: 10.1021/acs.est.2c04594
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Induced Interfacial Electron Transfer of Ferrihydrite under Oxic Conditions: Mineral Transformation and Redox Active Species Production

Abstract: Fe­(II)-catalyzed ferrihydrite transformation under anoxic conditions has been intensively studied, while such mechanisms are insufficient to be applied in oxic environments with depleted Fe­(II). Here, we investigated expanded pathways of sunlight-driven ferrihydrite transformation in the presence of dissolved oxygen, without initial addition of dissolved Fe­(II). We found that sunlight significantly facilitated the transformation of ferrihydrite to goethite compared to that under dark conditions. Redox activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…This experiment used deionized water (Milli-Q, Millipore, 18.2 MΩ•cm) to prepare all solutions. Following the previously reported procedures, 56 2-line ferrihydrite and ferrihydrite−OM coprecipitation with initial C/Fe molar ratios of 0−3 in the solution were synthesized. Pure ferrihydrite was synthesized by vigorously stirring (600 rpm) while adding 0.1 M NaOH to a 10 mM Fe(NO 3 ) 3 solution until a pH of 7 was reached.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This experiment used deionized water (Milli-Q, Millipore, 18.2 MΩ•cm) to prepare all solutions. Following the previously reported procedures, 56 2-line ferrihydrite and ferrihydrite−OM coprecipitation with initial C/Fe molar ratios of 0−3 in the solution were synthesized. Pure ferrihydrite was synthesized by vigorously stirring (600 rpm) while adding 0.1 M NaOH to a 10 mM Fe(NO 3 ) 3 solution until a pH of 7 was reached.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This experiment used deionized water (Milli-Q, Millipore, 18.2 MΩ•cm) to prepare all solutions. Following the previously reported procedures, 56 S1). S(-II)/Fe molar ratios of 0.1, 0.5, and 1.0 are hereinafter referred to as low sulfide, medium sulfide, and high sulfide conditions, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Furthermore, Fe is one of the most important accompanying elements of Tl, 65 with dozens to thousands of times higher concentrations than Tl in Tl-polluted waters. 9,66,67 The Fe(III)/Fe(II) cycle, which is well reported impacted by light, 19,68 can also influence Tl speciation in acidic sunlit environments. 3,10,17 As we previously reported that the generation of • OH from the Fe(III) photoreduction can induce Tl(I) oxidation under irradiated conditions, 17 we provided further insights here that the concentration ratios of Fe(III) and SRFA will significantly influence the redox transformations of Tl, with the rate and extent of Tl(I) photooxidation enhanced and Tl(III) photoreduction inhibited with increasing Fe(III) concentration (Figure S20).…”
Section: Environmental Implicationsmentioning
confidence: 95%
“…As a result, the formation of hydroxyl radicals (˚OH) and other reactive species, responsible for the degradation of the pollutant, will be improved. Also, photoelectrons can reduce dissolved oxygen and thus lead to the formation of radical superoxide ions 2 O −  according to Equation (4) [23].…”
Section: Influence Of Oxygen In the Airmentioning
confidence: 99%